1999
DOI: 10.1007/s002940050435
|View full text |Cite
|
Sign up to set email alerts
|

Starvation in yeast increases non-adaptive mutation

Abstract: The frequency of reversion in a histidine-requiring mutant of Saccharomyces cerevisiae increases about ten-fold in stationary cells during histidine starvation. Histidine starvation enhances a similar frequency of reversion in a tryptophan-requiring mutant. Starvation, therefore, enhances mutation frequencies in a non-adaptive manner. The base analogue 6-N-hydroxylaminopurine (HAP) added prior to plating on medium with limited histidine strongly increases reversion of the histidine mutant. HAP-induced reversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 0 publications
1
35
0
Order By: Relevance
“…On the other hand, the exact turning point of the population OD and the adaptation time depend on history. The adaptation timescale of 10 generations revealed by the chemostat and the reproducibility of the adaptation dynamics in separate experiments show that spontaneous mutations played no significant role in this phenomenon (Marini et al 1999).…”
Section: Resultsmentioning
confidence: 93%
“…On the other hand, the exact turning point of the population OD and the adaptation time depend on history. The adaptation timescale of 10 generations revealed by the chemostat and the reproducibility of the adaptation dynamics in separate experiments show that spontaneous mutations played no significant role in this phenomenon (Marini et al 1999).…”
Section: Resultsmentioning
confidence: 93%
“…2). This adaptation time is surprisingly shorter than those usually encountered in laboratory experiments involving the fixation of rare mutations in large populations of microorganisms, which were on the order of hundreds to thousands of generations (Luria and Delbruck, 1943;Paquin and Adams, 1983;Cairns et al, 1988;Lenski and Travisano, 1994;Drake et al, 1998;Marini et al, 1999;Elena and Lenski, 2003;Fong et al, 2005;Roth et al, 2006;Perfeito et al, 2007).…”
Section: The Population Growth Dynamics During Adaptationmentioning
confidence: 88%
“…The neo-Darwinian view extends this paradigm by maintaining that underlying the heritable phenotypic diversity are genes and genetic variation, which can be ascribed to neutral and advantageous mutations that occur rarely, spontaneously at random locations, and independently of any selection processes imposed by the environmental conditions. Since then, many studies demonstrated the importance of genetic variability that confers fitness advantage for the emergence of novel functional elements in a given selective environment (Luria and Delbruck, 1943;Paquin and Adams, 1983;Lenski and Travisano, 1994;Drake et al, 1998;Marini et al, 1999;Elena and Lenski, 2003;Fong et al, 2005;Maharjan et al, 2006;Perfeito et al, 2007).…”
mentioning
confidence: 99%
“…G2 regulation in response to diet/insulin signals also occurs in Drosophila male GSCs and in Caenorhabditis elegans germline precursors (Narbonne and Roy, 2006;Ueishi et al, 2009). Starvation promotes deleterious mutations during Saccharomyces cerevisae division (Marini et al, 1999), and cancer cells form repair foci during a delayed G2 upon DNA damage (Kao et al, 2001). The multitude of GSC G2 regulators might reflect a mechanism to ensure genomic integrity under poor dietary conditions.…”
Section: G2 Is a Major Point Of Gsc Proliferation Control By Diet-depmentioning
confidence: 99%